How to wow with PowerPoint - Harrington, Richard, 1972- (How to wow., 2007)
Go Beyond The Ordinary With Your Next Presentation ... provide a well-designed and rich multimedia experience! Wouldn't it be great if you could have two of the most sought-after graphic design professionals sitting next to you at your computer as you navigate through the infinite possibilities of your next important presentation? How to Wow with PowerPoint is the next best thing. It's the brainchild of Richard Harrington and Scott Rekdal, who have developed an incredible way to help you reach your full creative potential. A book for non-designers, Richard and Scott guide you step by step through realworld projects with an emphasis on cutting through the clutter and focusing on good design principles as a more effective way to build presentations. You'll receive tips and techniques on everything from selecting and preparing images to integrating sound and motion. Whether it's adding effective transitions to your slides or making the presentation technically sound and mobile, you'll be given the tools at every stage of the creative process in order to learn How to Wow! We begin with the important essentials of typography, layout, and design, and move on to creating tables, charts, graphs, and custom templates. Next comes the fun stuff, with projects focusing on audio and video files and integrating Flash. Finally, there is a chapter devoted to exporting and publishing, including how to create handouts, upload to the Web, and other ways to share your presentation. On the How to Wow CD-ROM is everything you'll need to complete the projects. The How to Wow CD-ROM Makes it a Snap! The How to Wow with PowerPoint companion CD at the back of this book contains all the files you'll need, including: Easy to use PowerPoint templates for each chapter to help you navigate through these projects and learn essential techniques. And you can modify the templates later for your own presentations. PLUS all the photographs, video and audio files used in the projects! Follow along with the lessons to dramatically increase your understanding of how these features are used and how they can be applied to your work, everyday! Extra presentation goodies that are ready to use such as stock photos, fonts, backgrounds, extra templates, and checklists to help you wow your audience.